Aplikasi Teknik Paper Stamp dan Pewarnaan Smock untuk Pengembangan Produk Batik Bonjer Magetan - Sarwono Sarwono; Sujadi Rahmat Hidayat; Tiwi Bina Affanti; Ratna Endah Santoso; M Rudianto (Institut Seni Indonesia Surakarta, 2025)
Batik Bonjer is a business group of low-income families engaged in batik production. The business has only been running for two years, and with members who have no background or experience in the field of batik, it is challenging to develop products. The ability to create products is often limited by initial training, which can result in underdeveloped products that are difficult to compete in the market. To overcome this problem, the PKM-UNS 2023 Team from RG Crafts and Innovation organized a program to enhance the capacity of Batik Bonjer's human resources in product development, utilizing paper stamp and smock coloring techniques. The activities carried out involve increasing human resource capacity and expanding and diversifying product offerings. This program successfully enhanced human resource capabilities in the production process, expanded product diversification, and increased sales. Keywords: batik, paper stamp, smock coloring, batik bonjer magetan